Piezoelectric ceramic material and preparation method thereof, and electronic device

By adopting specific chemical formulas of piezoelectric ceramic materials and adding metal oxides, the problem of high dielectric loss in high-frequency applications of existing lead-based piezoelectric ceramic materials is solved, and piezoelectric ceramic materials with low dielectric loss and high mechanical quality are achieved, which are suitable for high-frequency electronic devices.

CN119775003APending Publication Date: 2025-04-08HUAWEI TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311300596.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-08
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing lead-based piezoelectric ceramic materials have a large dielectric loss in high-frequency applications, resulting in reduced power conversion efficiency, increased heating and shortened life.

Method used

A piezoelectric ceramic material with the chemical general formula xPbTiO3-yPb0.7(La0.6Nd0.4)0.2TiO3-(1-x-y)Pb(Mn1/3Sb2/3)O3 is used, and metal oxides such as Co2O3, Fe2O3, NiO or MnO2 are added thereto, and the material components and structure are optimized through multiple pre-firing processes to reduce dielectric loss.

Benefits of technology

It realizes low dielectric loss of piezoelectric ceramic materials, reduces dielectric loss to below 0.8%, and the mechanical quality factor Qm is greater than 1800. It is suitable for high-frequency electronic devices, improving the power conversion efficiency and material stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775003A_ABST
    Figure CN119775003A_ABST
Patent Text Reader

Abstract

The present invention discloses a piezoelectric ceramic material and a preparation method thereof, and an electronic device. The chemical formula of the piezoelectric ceramic material is xPbTiO 3 ‑yPb 0.7 (La 0.6 Nd 0.4 ) 0.2 TiO 3 ‑(1‑x‑y)Pb(Mn 1 / 3 Sb 2 / 3 ) 3 , wherein 0.58≤x≤0.78, 0.2≤y≤0.4. The present application provides a piezoelectric ceramic material and a preparation method thereof, and an electronic device. The piezoelectric ceramic material can reduce dielectric loss, improve power conversion efficiency, reduce heat generation, and improve the stability of electronic devices in high-frequency applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electronic ceramic technology, and in particular, to piezoelectric ceramic materials and preparation methods thereof, and electronic devices. Background Art

[0002] Piezoelectric ceramic materials are materials with excellent performance, such as high piezoelectric coefficient and high stability. At present, piezoelectric ceramic materials have been widely used, especially in the fields of electronics and communications. A series of important progress has been made through the research on its preparation process, performance and application fields. Among them, lead-based piezoelectric ceramic materials prepared by chemical synthesis, solid-phase reaction, hydrothermal method and other methods have excellent performance and can meet the needs of different fields.

[0003] However, the common lead-based piezoelectric ceramic materials currently have the disadvantage of large dielectric loss in high-frequency applications, such as piezoelectric ultrasonic transducers and ultrasonic motors. Large dielectric loss will lead to reduced power conversion efficiency of piezoelectric ceramics, making it unable to perform at its best performance. It will also increase the heat generation of the ceramics and shorten the life of the piezoelectric ceramics.

[0004] The doped modified lead zirconate titanate piezoelectric ceramics provided by the prior art are represented by the following chemical formula:

[0005] xPb(Mg 1 / 3 Nb 2 / 3 )O3-yPb(Ni 1 / 3 Nb 2 / 3 )O3-(1-xy)Pb(Ti 1 / 2 Zr 1 / 2 )O 3+lSrCO3+mZnO+nQ, wherein Q is at least one of Li2CO3, CuO, SiO2, MnO2, Bi2O3, and La2O3. The sintering temperature of the doped modified lead zirconate titanate piezoelectric ceramic is about 900°C, the Curie temperature is 230°C, the electromechanical coupling coefficient Kp can reach 0.75, and the piezoelectric strain coefficient d33 can reach 700*10 -12 C / N, and the dielectric loss is less than 2%. However, the dielectric loss is still at a relatively high level and there is room for further improvement. In addition, the material formula is complex, which affects the piezoelectric performance of the material.

[0006] Therefore, reducing the dielectric loss of piezoelectric ceramic materials is very important for their high-frequency applications. Summary of the invention

[0007] The present application proposes a piezoelectric ceramic material and a preparation method thereof, and an electronic device, which can reduce dielectric loss, improve power conversion efficiency, reduce heat generation, and improve the stability of electronic devices in high-frequency applications.

[0008] In a first aspect, the present application provides a piezoelectric ceramic material, the chemical formula of which is xPbTiO3-yPb 0.7 (La 0.6 Nd 0.4 ) 0.2 TiO3-(1-xy)Pb(Mn 1 / 3 Sb 2 / 3 )O3, among which, 0.58≤x≤0.78, 0.2≤y≤0.4.

[0009] In some embodiments, the piezoelectric ceramic material has a general chemical formula of xPbTiO3-yPb 0.7 (La 0.6 Nd 0.4 ) 0.2 TiO3-(1-xy)Pb(Mn 1 / 3 Sb 2 / 3 )O3+mQ, Q is at least one of Co2O3, Fe2O3, NiO and MnO2, Q is in xPbTiO3-yPb 0.7 (La 0.6 Nd 0.4 ) 0.2 TiO3-(1-xy)Pb(Mn 1 / 3 Sb 2 / 3 )The mass percentage in O3 is m wt%, 0.1≤m≤8.

[0010] In some embodiments, Q is Co2O 3, 0.5%≤m≤5%.

[0011] In some embodiments, the piezoelectric ceramic material has a mechanical quality factor Qm greater than 1800.

[0012] In some embodiments, the piezoelectric ceramic material has a dielectric loss of less than 0.8% at 1000 Hz.

[0013] In a second aspect, the present application provides a method for preparing a piezoelectric ceramic material, the method comprising the following steps:

[0014] According to the chemical formula of the above piezoelectric ceramic material, weigh the powder raw materials of PbO, La2O3, Nd2O3, Sb2O3, TiO2 and MnO2, mix them with a dispersant and then perform a ball milling;

[0015] The ball milled product is dried and pre-fired once, and the pre-fired product after cooling is pre-fired N times, N≥2, to obtain ceramic powder;

[0016] The ceramic powder is mixed with a dispersant and subjected to secondary grinding. The secondary grinding product is mixed with a binder and then granulated and pressed to obtain a ceramic green sheet;

[0017] The ceramic green sheet is gradually heated to 1200° C. to 1240° C. for sintering, and then cooled to obtain a ceramic sheet;

[0018] A conductive layer is formed on the surface of the ceramic sheet and polarization treatment is performed to obtain a piezoelectric ceramic material.

[0019] In some embodiments, taking the powder raw material as 100%, the powder raw material includes 44.9%-68.4% lead oxide powder, 2.4%-2.5% lanthanum oxide powder, 0.2%-0.3% manganese dioxide powder, 0.6%-0.7% antimony oxide powder, 26.0%-50.0% titanium dioxide powder, 1.6%-1.8% neodymium oxide powder and 0.1%-8% Q powder in a mass ratio, and the Q powder includes at least one of Co2O3, Fe2O3, NiO and MnO2.

[0020] In some embodiments, the dispersant is anhydrous ethanol.

[0021] In some embodiments, the rotation speed of the ball milling is 200 r / min to 250 r / min, and the time of the ball milling is 1 h to 5 h.

[0022] In some embodiments, the particle size of the primary ball-milled product is 0.5 μm to 1 μm.

[0023] In some embodiments, the drying temperature of the first ball-milled product is 80°C to 150°C.

[0024] In some embodiments, the rotation speed of the secondary ball milling is 200 r / min to 250 r / min, and the time of the secondary ball milling is 1 h to 5 h.

[0025] In some embodiments, the amount of the binder is 6% to 8% of the total weight of the secondary ball-milled product.

[0026] In some embodiments, the binder is an aqueous solution of polyvinyl alcohol with a weight percentage of 8%.

[0027] In some embodiments, the ceramic green sheet has a thickness of 0.2 mm to 0.8 mm and a diameter of 8 mm to 12 mm.

[0028] In some embodiments, the primary pre-burning treatment specifically includes:

[0029] After the primary ball-milled product is dried, the temperature is increased to 700°C-750°C at 3°C / min-5°C / min and kept at that temperature for 1 hour. The temperature is then increased to 800°C-850°C at 2°C / min-2.5°C / min and kept at that temperature for 1 hour. The product is cooled to obtain a primary pre-calcined product.

[0030] In some embodiments, the N-times pre-burning treatment specifically includes:

[0031] The primary pre-sintered product is heated to 700°C-750°C at 3°C / min-5°C / min and kept warm for 1 hour, then heated to 880°C-920°C at 2°C / min-2.5°C / min and kept warm for 1 hour, and the pre-sintering treatment is repeated N times to obtain ceramic powder, N≥2.

[0032] In some embodiments, the gradient heating of the ceramic green sheet to 1100°C to 1140°C for sintering treatment specifically includes controlling the heating rate to be 3°C / min to 5°C / min, heating the ceramic green sheet to 800°C to 850°C, keeping it warm for 1h to 2h, and then continuing to heat it to 1200°C to 1240°C at 2°C / min to 2.5°C / min, and keeping it warm for 2h to 3h.

[0033] In some embodiments, a silver conductive layer is formed on the sintered ceramic sheet; and then polarization is performed in silicone oil at 110° C. under a direct current electric field with an electric field strength of 8 kV / mm for 20 minutes.

[0034] In a third aspect, the present application provides an electronic device, wherein the electronic device comprises the above-mentioned piezoelectric ceramic material.

[0035] Compared with the prior art, the piezoelectric ceramic material provided in the present application has low dielectric loss, the dielectric loss is reduced to below 0.8%, and the mechanical quality factor is above 1800. It has excellent performance of low dielectric loss and can be widely used in high-frequency electronic devices.

[0036] Furthermore, in xPbTiO3-yPb 0.7 (La 0.6 Nd 0.4 ) 0.2 TiO3-(1-xy)Pb(Mn 1 / 3 Sb 2 / 3 )Q-type oxides are added to the O3 ceramic material. The metal ion doping in the Q-type oxides can realize hard doping of the ternary piezoelectric ceramic material. The generated oxygen vacancies slowly diffuse to the domain wall, thereby pinning the domain wall, making it more difficult for the domain wall to move, causing a reduction in internal losses, and thus reducing the dielectric loss of the piezoelectric ceramic material.

[0037] The preparation method provided in this application can effectively control the grain size of the piezoelectric ceramic material and improve the density of the piezoelectric ceramic material by optimizing the raw material component formula of the piezoelectric ceramic material and effectively improving the particle uniformity of the mixed powder through N pre-sintering processes. The preparation process of this application is simple, the raw material components are clear, and the prepared piezoelectric ceramic material has low dielectric loss, and the dielectric loss is reduced to less than 0.8%. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 A schematic diagram of a process flow of a method for preparing a piezoelectric ceramic material provided in an embodiment of the present application;

[0039] Figure 2a This is an X-ray diffraction pattern of the piezoelectric ceramic material obtained in Example 1 of the present application;

[0040] Figure 2b This is an electronic image of the piezoelectric ceramic material obtained in Example 1 of the present application;

[0041] Figure 3a This is an X-ray diffraction pattern of the piezoelectric ceramic material obtained in Example 2 of the present application;

[0042] Figure 3b This is an electronic image of the piezoelectric ceramic material obtained in Example 2 of the present application;

[0043] Figure 4a This is an X-ray diffraction pattern of the piezoelectric ceramic material obtained in Example 3 of the present application;

[0044] Figure 4b This is an electronic image of the piezoelectric ceramic material obtained in Example 3 of the present application;

[0045] Figure 5 This is the effect of different contents of cobalt oxide on the dielectric loss of piezoelectric ceramic materials prepared in the examples of the present application. DETAILED DESCRIPTION

[0046] The technical solution provided by the present invention is further described below in conjunction with specific embodiments and comparative examples, but the present application is not limited to the following embodiments.

[0047] In order to better understand the technical solution of the present application, the embodiments of the present application are described in detail below with reference to the accompanying drawings.

[0048] It should be clear that the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0049] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.

[0050] Piezoelectric ceramic materials are materials with excellent performance, such as high piezoelectric coefficient and high stability. At present, piezoelectric ceramic materials have been widely used, especially in the fields of electronics and communications. A series of important progress has been made through the research on its preparation process, performance and application fields. Among them, lead-based piezoelectric ceramic materials prepared by chemical synthesis, solid-phase reaction, hydrothermal method and other methods have excellent performance and can meet the needs of different fields.

[0051] However, the common lead-based piezoelectric ceramic materials currently have the disadvantage of large dielectric loss in high-frequency applications, such as piezoelectric ultrasonic transducers and ultrasonic motors. Large dielectric loss will lead to reduced power conversion efficiency of piezoelectric ceramics, making it unable to perform at its best performance. It will also increase the heat generation of the ceramics and shorten the life of the piezoelectric ceramics.

[0052] Therefore, the present application provides a piezoelectric ceramic material, the chemical formula of which is xPbTiO3-yPb 0.7 (La 0.6 Nd 0.4 ) 0.2 TiO3-(1-xy)Pb(Mn 1 / 3 Sb 2 / 3 )O3, among which, 0.58≤x≤0.78, 0.2≤y≤0.4.

[0053] The piezoelectric ceramic material provided in the present application is of the perovskite type, has low dielectric loss, the dielectric loss is reduced to below 0.8%, and the mechanical quality factor is above 1800. It has excellent performance of low dielectric loss and can be widely used in high-frequency electronic devices.

[0054] As a further optional technical solution of the present application, the chemical formula of the piezoelectric ceramic material is xPbTiO3-yPb 0.7 (La 0.6 Nd 0.4 ) 0.2 TiO3-(1-xy)Pb(Mn 1 / 3 Sb 2 / 3 )O3+mQ, Q is at least one of Co2O3, Fe2O3, NiO and MnO2, Q is in xPbTiO3-yPb 0.7 (La 0.6 Nd 0.4 ) 0.2TiO3-(1-xy)Pb(Mn 1 / 3 Sb 2 / 3 )The mass percentage in O3 is m wt%, 0.1≤m≤8.

[0055] Understandably, in xPbTiO3-yPb 0.7 (La 0.6 Nd 0.4 ) 0.2 TiO3-(1-xy)Pb(Mn 1 / 3 Sb 2 / 3 )Q-type oxides are added to the O3 ceramic material. The metal ion doping in the Q-type oxides can realize hard doping of the ternary piezoelectric ceramic material. The generated oxygen vacancies slowly diffuse and move toward the domain wall. The spatial negative charges generated by the oxygen vacancies can pin the domain wall, making it more difficult for the domain wall to move. The piezoelectric material is not easy to polarize, resulting in a reduction in internal friction loss, thereby reducing the dielectric loss of the piezoelectric ceramic material.

[0056] In the present application, the molar content of PbTiO3 lead titanate in the piezoelectric ceramic material can specifically be 58 mol%, 60 mol%, 62 mol%, 64 mol%, 65 mol%, 68 mol%, 70 mol%, 72 mol%, 75 mol%, 78 mol%, etc., and of course it can also be any value between 58 mol% and 78 mol%, which is not limited here.

[0057] Pb in piezoelectric ceramic materials 0.7 (La 0.6 Nd 0.4 ) 0.2 TiO3 is one of the components. Pb 0.7 (La 0.6 Nd 0.4 ) 0.2 The molar content of TiO3 can be 20mol%, 21mol%, 22mol%, 24mol%, 25mol%, 26mol%, 28mol%, 30mol%, 32mol%, 35mol%, 38mol% or 40mol%, etc., and can also be any value between 20mol% and 40mol%, which is not limited here. 1 / 3 Sb 2 / 3 )O3, as one of the components, can improve the piezoelectric properties of piezoelectric ceramic materials.

[0058] In some embodiments, in the piezoelectric ceramic material, Q is in the range of xPbTiO3-yPb 0.7 (La 0.6 Nd 0.4 ) 0.2TiO3-(1-xy)Pb(Mn 1 / 3 Sb 2 / 3 ) The mass percentage of Co in Q metal oxide is m, and the mass percentage (doping amount) of Q metal oxide can be 0.1wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 6wt%, 7wt% or 8wt%, etc., and of course, it can also be any value between 0.1wt% and 8wt%, which is not limited here. 3+ , Fe 3+ 、Ni 2+ , Mn 4+ Metal ions replace Ti in piezoelectric ceramic materials 4+ In order to maintain the electrical neutrality of the unit cell, the total valence of the negative ions in the unit cell needs to be reduced, resulting in the formation of oxygen vacancies; oxygen vacancies may cause the skeleton of the unit cell oxygen octahedron to collapse, thereby reducing the unit cell size, further controlling the grain size of the ceramic material, improving the density of the ceramic material, making the doping more uniform, and reducing the dielectric loss. Preferably, 0.5wt%≤m≤5wt%.

[0059] In some embodiments, the Q-type metal oxide is selected from Co2O3.

[0060] In some embodiments, the piezoelectric ceramic material has a mechanical quality factor Qm greater than 1800.

[0061] In some embodiments, the dielectric loss of the piezoelectric ceramic material at 1000 Hz is less than 0.8%, and specifically may be 0.32, 0.45, 0.56, 0.53, 0.59, 0.61, 0.67, 0.78, etc., which is not limited here.

[0062] The piezoelectric ceramic material provided by the present application can be widely used in various industries in electronic materials. The piezoelectric effect can be used to prepare electronic devices such as piezoelectric power supplies, piezoelectric sensors, piezoelectric speakers, ultrasonic generators, piezoelectric gyroscopes, piezoelectric resonators, and piezoelectric relays, without limitation.

[0063] The present application also provides a method for preparing a piezoelectric ceramic material, such as Figure 1 As shown, the method comprises the following steps:

[0064] S10, according to the chemical formula of the piezoelectric ceramic material, weigh the powder raw materials of PbO, La2O3, Nd2O3, Sb2O3, TiO2 and MnO2, mix them with a dispersant and then perform a ball milling;

[0065] S20, drying the ball milled product and performing a pre-calcination treatment, and then cooling the pre-calcined product and performing N pre-calcination treatments again, N ≥ 2, to obtain ceramic powder;

[0066] S30, mixing the ceramic powder with a dispersant, and performing secondary grinding, mixing the secondary grinding product with a binder, granulating, and pressing to obtain a ceramic green sheet;

[0067] S40, gradually heating the ceramic green sheet to 1200° C. to 1240° C. for sintering, and cooling to obtain a ceramic sheet;

[0068] S50, forming a conductive layer on the surface of the ceramic sheet and performing polarization treatment to obtain a piezoelectric ceramic material.

[0069] The preparation method provided in this application can effectively control the grain size of the piezoelectric ceramic material and improve the density of the piezoelectric ceramic material by optimizing the raw material component formula of the piezoelectric ceramic material and effectively improving the particle uniformity of the mixed powder through N pre-sintering processes. The preparation process of this application is simple, the raw material components are clear, and the prepared piezoelectric ceramic material has low dielectric loss, and the dielectric loss is reduced to less than 0.8%.

[0070] S10, according to the general chemical formula of piezoelectric ceramic materials, weigh the powder raw materials of PbO, La2O3, Nd2O3, Sb2O3, TiO2 and MnO2, mix them with a dispersant and then perform a ball milling.

[0071] In some embodiments, taking the powder raw material as 100%, the powder raw material includes 44.9%-68.4% lead oxide powder, 2.4%-2.5% lanthanum oxide powder, 0.2%-0.3% manganese dioxide powder, 0.6%-0.7% antimony oxide powder, 26.0%-50.0% titanium dioxide powder, 1.6%-1.8% neodymium oxide powder and 0.1%-1% Q powder in a mass ratio, and the Q powder includes at least one of Co2O3, Fe2O3, NiO and MnO2.

[0072] Specifically, metal ions in Q-type oxides are doped into xPbTiO3-yPb 0.7 (La 0.6 Nd 0.4 ) 0.2 TiO3-(1-xy)Pb(Mn 1 / 3 Sb 2 / 3 )O3 ceramic materials are hard doped, and the generated oxygen vacancies slowly diffuse toward the domain walls, thereby pinning the domain walls, making it more difficult for the domain walls to move, causing a reduction in internal losses, and thus reducing the dielectric loss of the piezoelectric ceramic material.

[0073] Specifically, the dispersant is anhydrous ethanol. In other embodiments, the dispersant may also be deionized water or the like.

[0074] The powder raw material is subjected to a ball milling, and zirconium balls are used for the first ball milling. The amount of dispersant used is 1 to 2 times the total weight of the powder raw material and the zirconium balls; specifically, it can be 1 times, 1.5 times, 1.7 times, 1.8 times, 2 times, etc., which is not limited here.

[0075] In some embodiments, the rotation speed of the ball milling is 200 r / min to 250 r / min, and the time of the ball milling is 1 h to 5 h.

[0076] S20, drying the ball milled product once and then pre-firing it once, and then pre-firing the cooled pre-firing product N times, N≥2, to obtain ceramic powder.

[0077] In some embodiments, the drying temperature of the primary ball-milled product is 80°C to 150°C, specifically 80°C, 90°C, 100°C, 120°C, 140°C or 150°C, etc. The drying time can be 1h, 2h, 3h, 4h, 5h, 6h, etc., and of course it can also be other values ​​within the above range, which is not limited here.

[0078] Specifically, the primary pre-sintering treatment specifically includes: drying the primary ball milled product, heating it to 700°C to 750°C at 3°C / min to 5°C / min, keeping it for 1 hour, then heating it to 800°C to 850°C at 2°C / min to 2.5°C / min, keeping it for 1 hour, and cooling it to obtain the primary pre-sintered product. It can be understood that low-temperature pre-sintering can inhibit the volatilization of PbO during the sintering process, so that the piezoelectric ceramic material can have excellent piezoelectric properties.

[0079] Furthermore, the N-times pre-burning process specifically includes:

[0080] The primary pre-sintered product is heated to 700°C-750°C at 3°C / min-5°C / min and kept warm for 1 hour, then heated to 880°C-920°C at 2°C / min-2.5°C / min and kept warm for 1 hour, and the pre-sintering treatment is repeated N times to obtain ceramic powder, N≥2.

[0081] The present application adopts multiple pre-firing processes, which can improve the uniformity of the mixed powder compared to a single pre-firing, thereby improving the uniformity of the piezoelectric ceramic composition and improving the reliability of the piezoelectric device.

[0082] S30, mixing the ceramic powder with the dispersant, and performing secondary grinding, mixing the secondary grinding product with the binder, granulating, and pressing to obtain a ceramic green sheet.

[0083] The dispersant used in the secondary ball milling is anhydrous ethanol. In other embodiments, the dispersant may also be deionized water, etc. The secondary ball milling can further improve the uniformity of each component in the ceramic powder and improve the reliability of the piezoelectric device.

[0084] The ceramic powder is subjected to secondary ball milling using zirconium balls. The amount of dispersant used is 0.5 to 2 times the total weight of the ceramic powder; specifically, it can be 0.5, 0.7, 0.8, 1, 1.5, 2, etc., and is not limited here.

[0085] In some embodiments, the rotation speed of the secondary ball milling is 200 r / min to 250 r / min, and the time of the secondary ball milling is 1 h to 5 h.

[0086] In some embodiments, the amount of the binder is 6% to 8% of the total weight of the secondary ball-milled product; specifically, it can be 6%, 6.5%, 7%, 7.2%, 7.5%, 7.8% or 8%, etc., which is not limited here.

[0087] In the present application, the binder is a polyvinyl alcohol aqueous solution with a weight percentage of 8%;

[0088] The ceramic green sheet has a thickness of 0.2 mm to 0.8 mm and a diameter of 8 mm to 12 mm.

[0089] S40, gradually heating the ceramic green sheet to 1200° C. to 1240° C. for sintering, and cooling to obtain a ceramic sheet;

[0090] Specifically, the ceramic green sheet is gradually heated to 1100°C to 1140°C for sintering, specifically including controlling the heating rate to be 3°C / min to 5°C / min, heating the ceramic green sheet to 800°C to 850°C, keeping the temperature for 1h to 2h, and then continuing to heat to 1200°C to 1240°C at 2°C / min to 2.5°C / min, keeping the temperature for 2h to 3h. Then, the ceramic sheet is naturally cooled in the furnace to obtain the ceramic sheet.

[0091] S50, forming a conductive layer on the surface of the ceramic sheet and performing polarization treatment to obtain a piezoelectric ceramic material.

[0092] In some embodiments, a conductive paste may be coated on the sintered ceramic sheet. The conductive paste may be a conductive silver paste, a conductive copper paste, etc., which is not limited here.

[0093] Specifically, a silver conductive layer was formed on a ceramic sheet; and then polarized in silicone oil at 110° C. under a direct current electric field with an electric field strength of 8 kV / mm for 20 minutes.

[0094] The following is a further description of the embodiments of the present invention in multiple embodiments. The embodiments of the present invention are not limited to the following specific embodiments. The embodiments can be appropriately modified within the scope of the unchanged main rights.

[0095] Example 1

[0096] A method for preparing a piezoelectric ceramic material comprises the following steps:

[0097] (1) Weigh 21.0 g of lead oxide powder, 0.8 g of lanthanum oxide powder, 0.1 g of manganese dioxide powder, 0.2 g of antimony oxide powder, 8.0 g of titanium dioxide powder, 0.5 g of neodymium oxide powder and 0.03 g of cobalt oxide powder (0.1% by mass) and mix them. Add 150 g of zirconium oxide ball milling beads and 200 ml of anhydrous ethanol, put them into a ball milling jar, and use a planetary ball mill to perform ball milling at a speed of 300 rpm for 15 hours. After ball milling, filter out the ball milling beads, and dry the remaining slurry for 24 hours to obtain a mixed powder.

[0098] (2) The mixed powder is sieved through a 60-mesh sieve and placed in a crucible, and pre-fired in a muffle furnace: the temperature is raised to 700°C at 4°C / min and kept for one hour, and then the temperature is raised to 850°C at 2°C / min and kept for one hour; after the powder is cooled to room temperature, it is pre-fired again: the temperature is raised to 700°C at 4°C / min and kept for one hour, and then the temperature is raised to 900°C at 2°C / min and kept for one hour to obtain a ceramic material.

[0099] (3) The ceramic material is subjected to a second ball milling, with the same steps as the first ball milling, and the ball milling beads are filtered, and the remaining slurry is dried for 24 hours to obtain the ceramic material.

[0100] (4) Add an appropriate amount of 8% by volume polyvinyl alcohol (PVA) solution to the ceramic material for granulation. After granulation, the powder is sieved through a 60-mesh sieve, and the sieved powder is pressed into a ceramic sheet with a diameter of 10 mm and a thickness of 0.6 mm by dry pressing.

[0101] (5) Place the ceramic sheet in a lead-containing pad in a crucible and sinter it in a muffle furnace: raise the temperature to 850°C at 3°C / min and keep it for one hour, then raise the temperature to 1210°C at 2°C / min and keep it for two hours; coat the sintered ceramic sheet with medium-temperature silver paste and sinter it, and then polarize it in 110°C silicone oil with an electric field of 8kv / mm to obtain a piezoelectric ceramic sheet.

[0102] Figure 2a This is the X-ray diffraction pattern of the piezoelectric ceramic material obtained in Example 1 of the present application; the general formula of the piezoelectric ceramic material is 0.58PbTiO3-0.4Pb 0.7 (La 0.6 Nd 0.4) 0.2 TiO3-0.02Pb(Mn 1 / 3 Sb 2 / 3 )O3+0.1wt%C2O3. Figure 2b This is an electronic image of the piezoelectric ceramic material obtained in Example 1 of the present application; Figure 2b As shown, the piezoelectric ceramic material has uniform grain size, clear grain boundaries, few pores, and a uniform and dense structure.

[0103] Example 2

[0104] A method for preparing a piezoelectric ceramic material comprises the following steps:

[0105] (1) Weigh 21.0 g of lead oxide powder, 0.8 g of lanthanum oxide powder, 0.1 g of manganese dioxide powder, 0.2 g of antimony oxide powder, 8.0 g of titanium dioxide powder, 0.5 g of neodymium oxide powder and 0.15 g of cobalt oxide powder (0.5% by mass) and mix them, add 150 g of zirconium oxide ball milling beads and 200 ml of anhydrous ethanol, put them into a ball milling jar, and use a planetary ball mill to perform ball milling at a ball milling speed of 300 rpm for 15 hours; after ball milling, filter out the ball milling beads, and dry the remaining slurry for 24 hours to obtain a mixed powder.

[0106] (2) The mixed powder is sieved through a 60-mesh sieve and placed in a crucible, and pre-fired in a muffle furnace: the temperature is raised to 700°C at 4°C / min and kept for one hour, and then the temperature is raised to 850°C at 2°C / min and kept for one hour; after the powder is cooled to room temperature, it is pre-fired again: the temperature is raised to 750°C at 4°C / min and kept for one hour, and then the temperature is raised to 900°C at 2°C / min and kept for one hour to obtain a ceramic material.

[0107] (3) The ceramic material is subjected to a second ball milling, with the same steps as the first ball milling, and the ball milling beads are filtered, and the remaining slurry is dried for 24 hours to obtain the ceramic material.

[0108] (4) Add an appropriate amount of 8% by volume polyvinyl alcohol (PVA) solution to the ceramic material for granulation. After granulation, the powder is sieved through a 60-mesh sieve, and the sieved powder is pressed into a ceramic sheet with a diameter of 10 mm and a thickness of 0.6 mm by dry pressing.

[0109] (5) Place the ceramic sheet in a lead-containing pad in a crucible and sinter it in a muffle furnace: raise the temperature to 850°C at 3°C / min and keep it for one hour, then raise the temperature to 1210°C at 2°C / min and keep it for two hours; coat the sintered ceramic sheet with medium-temperature silver paste and sinter it, and then polarize it in 110°C silicone oil with an electric field of 8kv / mm to obtain a piezoelectric ceramic sheet.

[0110] Figure 3aThis is the X-ray diffraction pattern of the piezoelectric ceramic material obtained in Example 2 of the present application; the general formula of the piezoelectric ceramic material is 0.58PbTiO3-0.4Pb 0.7 (La 0.6 Nd 0.4 ) 0.2 TiO3-0.02Pb(Mn 1 / 3 Sb 2 / 3 )O3+0.5wt%C2O3. Figure 3b This is an electronic image of the piezoelectric ceramic material obtained in Example 2 of the present application; Figure 3b As shown, the piezoelectric ceramic material has uniform grain size, clear grain boundaries, few pores, and a uniform and dense structure.

[0111] Example 3

[0112] A method for preparing a piezoelectric ceramic material comprises the following steps:

[0113] (1) Weigh 21.0 g of lead oxide powder, 0.8 g of lanthanum oxide powder, 0.1 g of manganese dioxide powder, 0.2 g of antimony oxide powder, 8.0 g of titanium dioxide powder, 0.5 g of neodymium oxide powder and 0.3 g of cobalt oxide powder (1.0% by mass) and mix them. Add 150 g of zirconium oxide ball milling beads and 200 ml of anhydrous ethanol, put them into a ball milling jar, and use a planetary ball mill to perform ball milling at a ball milling speed of 300 rpm for 15 hours. After ball milling, filter out the ball milling beads, and dry the remaining slurry for 24 hours to obtain a mixed powder.

[0114] (2) The mixed powder is sieved through a 60-mesh sieve and placed in a crucible, and pre-fired in a muffle furnace: the temperature is raised to 700°C at 4°C / min and kept for one hour, and then the temperature is raised to 850°C at 2°C / min and kept for one hour; after the powder is cooled to room temperature, it is pre-fired for a second time: the temperature is raised to 720°C at 4°C / min and kept for one hour, and then the temperature is raised to 920°C at 2°C / min and kept for one hour to obtain a ceramic material.

[0115] (3) The ceramic material is subjected to a second ball milling, with the same steps as the first ball milling, and the ball milling beads are filtered, and the remaining slurry is dried for 24 hours to obtain the ceramic material.

[0116] (4) Add an appropriate amount of 8% by volume polyvinyl alcohol (PVA) solution to the ceramic material for granulation. After granulation, the powder is sieved through a 60-mesh sieve, and the sieved powder is pressed into a ceramic sheet with a diameter of 10 mm and a thickness of 0.6 mm by dry pressing.

[0117] (5) Place the ceramic sheet in a lead-containing pad in a crucible and sinter it in a muffle furnace: raise the temperature to 850°C at 3°C / min and keep it for one hour, then raise the temperature to 1210°C at 2°C / min and keep it for two hours; coat the sintered ceramic sheet with medium-temperature silver paste and sinter it, and then polarize it in 110°C silicone oil with an electric field of 8kv / mm to obtain a piezoelectric ceramic sheet.

[0118] Figure 4a This is the X-ray diffraction pattern of the piezoelectric ceramic material obtained in Example 3 of the present application; the general formula of the piezoelectric ceramic material is 0.58PbTiO3-0.4Pb 0.7 (La 0.6 Nd 0.4 ) 0.2 TiO3-0.02Pb(Mn 1 / 3 Sb 2 / 3 )O3+0.5wt%C2O3. Figure 4b This is an electronic image of the piezoelectric ceramic material obtained in Example 3 of the present application; Figure 4b As shown, the piezoelectric ceramic material has uniform grain size, clear grain boundaries, few pores, and a uniform and dense structure.

[0119] Example 4

[0120] The difference from Example 1 is that in step (1), 21.0 g of lead oxide powder, 0.8 g of lanthanum oxide powder, 0.1 g of manganese dioxide powder, 0.2 g of antimony oxide powder, 8.0 g of titanium dioxide powder, 0.5 g of neodymium oxide powder and 1.5 g of cobalt oxide powder (5% by mass) are weighed and mixed, 150 g of zirconium oxide ball milling beads and 200 ml of anhydrous ethanol are added, the mixture is put into a ball milling jar, and ball milling is performed using a planetary ball mill at a ball milling speed of 300 rpm for 15 hours; after ball milling, the ball milling beads are filtered out, and the remaining slurry is dried for 24 hours to obtain a mixed powder.

[0121] Example 5

[0122] The difference from Example 1 is that in step (1), 21.0 g of lead oxide powder, 0.8 g of lanthanum oxide powder, 0.1 g of manganese dioxide powder, 0.2 g of antimony oxide powder, 8.0 g of titanium dioxide powder, 0.5 g of neodymium oxide powder and 2.45 g of cobalt oxide powder (8% by mass) are weighed and mixed, 150 g of zirconium oxide ball milling beads and 200 ml of anhydrous ethanol are added, the mixture is put into a ball milling jar, and ball milling is performed using a planetary ball mill at a ball milling speed of 300 rpm for 15 hours; after ball milling, the ball milling beads are filtered out, and the remaining slurry is dried for 24 hours to obtain a mixed powder.

[0123] Example 6

[0124] The difference from Example 1 is that the amount of raw materials added is different, so that the final prepared pressure ceramic material is 0.7PbTiO3-0.3Pb 0.7 (La 0.6 Nd 0.4 ) 0.2 TiO3-0.1Pb(Mn 1 / 3 Sb 2 / 3 )O3+0.5wt%C2O3.

[0125] Example 7

[0126] The difference from Example 1 is that in step (1), 0.15 g of iron oxide Fe2O3 is used instead of cobalt oxide Co2O3 powder (0.5% by mass) for mixing.

[0127] Example 8

[0128] The difference from Example 1 is that in step (1), 0.15 g of nickel oxide NiO is used instead of cobalt oxide Co2O3 powder (0.5% by mass) for mixing.

[0129] Example 9

[0130] The difference from Example 1 is that in step (1), 0.15 g of manganese oxide MnO 2 is used instead of cobalt oxide Co 2 O 3 powder (0.5% by mass) for mixing.

[0131] Example 10

[0132] Different from Example 1, no cobalt oxide Co2O3 powder is added in step (1).

[0133] Comparative Example 1

[0134] Directly use commercial PbZr 0.52 Ti 0.48 O3 (PZT) ceramic powder is used as the piezoelectric ceramic material.

[0135] Performance Testing:

[0136] (1) Morphological characteristics of piezoelectric ceramic materials

[0137] The morphology of the piezoelectric ceramic material was analyzed using a scanning electron microscope to obtain its scanning electron microscope image.

[0138] (2) Phase composition of piezoelectric ceramic materials

[0139] The phase composition of the piezoelectric ceramic powder was analyzed by X-ray diffractometer, and the test parameters were: 10°~80°, scanning rate 5° / min, and step length 0.020°.

[0140] (3) Dielectric properties test of piezoelectric ceramic materials

[0141] The piezoelectric ceramic sample with good electrodes was placed on an Agilent 4192A impedance analyzer to test the capacitance and dielectric loss at a test frequency of 1kHz and a small signal voltage of 1V at room temperature. The relative dielectric constant εr of the piezoelectric ceramic material was then calculated according to formula (1):

[0142]

[0143] In this formula, C x is the material capacitance value, h is the thickness of the sample, and D is the diameter of the upper and lower surfaces of the sample.

[0144] (4) Dielectric loss tanδ test of piezoelectric ceramic materials at 1000Hz:

[0145] The capacitance and dielectric loss values ​​at 1kHz and different electric field strengths (1kV / cm, 2kV / cm, 3kV / cm, 4kV / cm and 5kV / cm) were measured by the QS89 strong field loss tester produced by Shanghai Yanggao Electric Co., Ltd., and the relative dielectric constant under strong electric field was calculated according to formula (1). As the applied field strength increases, the strong field dielectric constant and dielectric loss also increase, and the strong field dielectric loss value at the maximum field strength of 5kV / cm is obtained.

[0146] Table 1. Performance tests of piezoelectric ceramic materials prepared in various embodiments and comparative examples

[0147]

[0148] According to Examples 1 to 8, it can be seen that in PbTiO3-Pb 0.7 (La 0.6 Nd 0.4 ) 0.2 TiO3-Pb(Mn 1 / 3 Sb 2 / 3 )O3In this ternary piezoelectric ceramic material, Q-type oxides and metal ions (Co 3+ , Fe 3+ 、Ni 2+ , Mn 4+ The piezoelectric ceramic material provided by the present application has low dielectric loss, the dielectric loss is reduced to less than 0.8%, and the mechanical quality factor Qm reaches more than 1800.

[0149] According to the test data of Examples 1 to 5, the addition amount of Co2O3 in the ternary piezoelectric ceramic material is further preferably 0.1% to 5%, and more preferably 0.5%.

[0150] According to the test data of Example 10, the PbTiO3-Pb 0.7 (La 0.6 Nd 0.4 ) 0.2 TiO3-Pb(Mn 1 / 3 Sb 2 / 3 )O3This ternary piezoelectric ceramic material can achieve lower dielectric loss even without adding Co2O3, which is lower than the commercial PbZr 0.52 Ti 0.48 O3(PZT) ceramic powder also decreased significantly.

[0151] Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the claims. Any technical personnel in this field may make several possible changes and modifications without departing from the concept of the present application. Therefore, the scope of protection of the present application shall be based on the scope defined by the claims of the present application.

Claims

1. A piezoelectric ceramic material, characterized in that: The chemical formula of the piezoelectric ceramic material is xPbTiO3-yPb 0.7 (La 0.6 Nd 0.4 ) 0.2 TiO3-(1-xy)Pb(Mn 1 / 3 Sb 2 / 3 )O3, among which, 0.58≤x≤0.78, 0.2≤y≤0.

4.

2. The piezoelectric ceramic material according to claim 1, characterized in that The chemical formula of the piezoelectric ceramic material is xPbTiO3-yPb 0.7 (La 0.6 Nd 0.4 ) 0.2 TiO3-(1-xy)Pb(Mn 1 / 3 Sb 2 / 3 )O3+mQ, Q is at least one of Co2O3, Fe2O3, NiO and MnO2, Q is in xPbTiO3-yPb 0.7 (La 0.6 Nd 0.4 ) 0.2 TiO3-(1-xy)Pb(Mn 1 / 3 Sb 2 / 3 )The mass percentage in O3 is m wt%, 0.1≤m≤8.

3. The piezoelectric ceramic material according to claim 2, characterized in that: Q is Co2O3, 0.5%≤m≤5%.

4. The piezoelectric ceramic material according to any one of claims 1 to 3, wherein: It meets at least one of the following characteristics: a) the mechanical quality factor Qm of the piezoelectric ceramic material is greater than 1800; b) The dielectric loss of the piezoelectric ceramic material at 1000 Hz is less than 0.8%.

5. A method for preparing a piezoelectric ceramic material, characterized in that: The method comprises the following steps, According to the chemical formula of the piezoelectric ceramic material according to any one of claims 1 to 4, weigh the powder raw materials of PbO, La2O3, Nd2O3, Sb2O3, TiO2 and MnO2, mix them with a dispersant and then perform a ball milling; The ball milled product is dried and then pre-fired once, and the pre-fired product after cooling is pre-fired again N times, where N is greater than or equal to 2, to obtain ceramic powder; The ceramic powder is mixed with a dispersant and subjected to secondary grinding. The secondary grinding product is mixed with a binder and then granulated and pressed to obtain a ceramic green sheet. Gradually heating the ceramic green sheet to 1200° C. to 1240° C. for sintering, and cooling to obtain a ceramic sheet; A conductive layer is formed on the surface of the ceramic sheet and polarized to obtain a piezoelectric ceramic material.

6. The method for preparing a piezoelectric ceramic material according to claim 5, characterized in that: Taking the powder raw material as 100%, the powder raw material includes 44.9%-68.4% lead oxide powder, 2.4%-2.5% lanthanum oxide powder, 0.2%-0.3% manganese dioxide powder, 0.6%-0.7% antimony oxide powder, 26.0%-50.0% titanium dioxide powder, 1.6%-1.8% neodymium oxide powder and 0.1%-8% Q powder in a mass ratio, and the Q powder includes at least one of Co2O3, Fe2O3, NiO and MnO2.

7. The method for preparing a piezoelectric ceramic material according to claim 5 or 6, characterized in that: The method satisfies at least one of the following characteristics: a) the dispersant is anhydrous ethanol; b) The speed of the ball milling is 200 rpm to 250 rpm, and the time of the ball milling is 1 h to 5 h; c) the particle size of the primary milling product is 0.5 μm to 1 μm; d) the drying temperature of the once-milled product is 80° C. to 150° C.; e) The speed of the secondary ball milling is 200 rpm to 250 rpm, and the time of the secondary ball milling is 1 h to 5 h; f) the amount of the binder is 6% to 8% of the total weight of the secondary ball-milled product; g) the binder is an 8% by weight polyvinyl alcohol aqueous solution; h) The thickness of the ceramic green sheet is 0.2 mm to 0.8 mm, and the diameter is 8 mm to 12 mm.

8. The method for preparing a piezoelectric ceramic material according to claim 5 or 6, characterized in that: The primary pre-burning treatment specifically includes: After drying the primary ball-milled product, the temperature was raised to 700°C-750°C at a rate of 3°C / min-5°C / min and kept at that temperature for 1 hour. The temperature was then raised to 800°C-850°C at a rate of 2°C / min-2.5°C / min and kept at that temperature for 1 hour. The product was then cooled to obtain a primary calcined product.

9. The method for preparing a piezoelectric ceramic material according to claim 5 or 6, characterized in that: The N-times pre-burning process specifically includes: The primary pre-fired product is heated to 700°C to 750°C at a rate of 3°C / min to 5°C / min and kept warm for 1 hour, then heated to 880°C to 920°C at a rate of 2°C / min to 2.5°C / min and kept warm for 1 hour. The pre-fired process is repeated N times to obtain ceramic powder, where N≥2.

10. The method for preparing a piezoelectric ceramic material according to claim 5 or 6, characterized in that: The ceramic green sheet is gradually heated to 1100°C to 1140°C for sintering, specifically including controlling the heating rate to be 3°C / min to 5°C / min, heating the ceramic green sheet to 800°C to 850°C, keeping the temperature for 1h to 2h, and then continuing to heat the ceramic green sheet to 1200°C to 1240°C at a rate of 2°C / min to 2.5°C / min, and keeping the temperature for 2h to 3h.

11. The method for preparing a piezoelectric ceramic material according to claim 5 or 6, characterized in that: A silver conductive layer was formed on the sintered ceramic sheet; the sheet was then polarized in silicone oil at 110° C. under a DC electric field with an electric field strength of 8 kV / mm for 20 minutes.

12. An electronic device, characterized in that: The electronic device comprises the piezoelectric ceramic material according to any one of claims 1 to 4.